ANALISA KETERSEDIAN AIR BENDUNG MENCONGAH KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - APRILIA KII WENAMAYA; MUHAMAD YAMIN; AMINULLAH AMINULLAH; NI MADE NIA BUNGA SURYA DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
The purpose of this study is to determine the availability of air that can be used for air irrigation needs for the Mencongah Weir Irrigation area and to determine the amount of air needed for Mencongah Weir irrigation. The method used is the Normal method, Log Person II and Gumbel. The results of this study indicate that the availability of air at the Mencongah Weir during the growing season is still sufficient, where the availability of air at the Mencongah Weir during the growing season is still sufficient, where the air supply (QMin) = 79.04lt/sec/ha which occurred in March. While the maximum discharge (Qmak) = 249.88 lt/sec/ha in August and the minimum water demand discharge (QMin) = 75.7 lt/sec/ha which occurred in November. While the maximum discharge (Qmak) = 127.94 lt/sec/ha in August.